2019
DOI: 10.1259/bjr.20190551
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy success and outcomes after uterine fibroid embolization: updated review of published literature

Abstract: Females with symptomatic leiomyomas (fibroids) wishing to maintain fertility are faced with difficult treatment choices. These include uterine fibroid embolization (UFE), myomectomy, hormonal therapy, MRI high intensity focused ultrasound, and myolysis. This review focuses on UFE, one of the most commonly accepted minimally invasive procedural choices among patients with symptomatic fibroids wishing to retain the option of becoming pregnant in the future, and makes comparisons to myomectomy which has historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
1
23
0
3
Order By: Relevance
“…UAE is a frequently used technique which reduces length of hospital stay and pain compared to the operation and patients rapidly return to the daily usual activities. However, UAE has the risk of reintervention, and lower pregnancy and live birth rates [13].…”
Section: Discussionmentioning
confidence: 99%
“…UAE is a frequently used technique which reduces length of hospital stay and pain compared to the operation and patients rapidly return to the daily usual activities. However, UAE has the risk of reintervention, and lower pregnancy and live birth rates [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Torre et al [41], which included 66 women treated with UAE, showed that only 1 woman became pregnant, and she finally miscarried, although the ovarian reserve was unchanged after UAE, demonstrating that the negative impact on fertility might not be related to ovarian function. A review [42] of pregnancy outcomes after UAE concluded that low birth weight, miscarriage, and prematurity have been associated with UAE. Carranza-Mamane et al [43] also showed that there were lower pregnancy rates, higher miscarriage rates, and more adverse pregnancy outcomes after UAE than after myomectomy.…”
Section: Figmentioning
confidence: 99%
“…Six of the articles solely explored pregnancy outcomes after uterine artery embolization. [3][4][5][6][7][8] The remaining two manuscripts were reviews that compared uterine artery embolization to myomectomy. 9,10 Firouznia et.…”
Section: Related Literaturementioning
confidence: 99%
“…Ludwig et al conducted a review focused on uterine fibroid embolization to compare it to the historically suggested myomectomy. 5 Publications were selected based on relevance of information to fertility and pregnancy without being limited to single case reports. The article had 52 references, of which 7 were randomized controlled trials.…”
Section: Related Literaturementioning
confidence: 99%